Vaxi-eTrack: A Data-driven System for Infant Vaccination Management for Barangay Clinic Pico La Trinidad, Benguet - Jayren Acebes; Jerick Brell Amiao; Sandra Calias; Marielle Angela Fianza-Buya; Linson Ganado (Southeast Asian Journal of Science and Technology, 2025)
Efficient management of infant immunization remains a significant challenge in rural communitiesin the Philippines, where vaccination processes continue to rely on manual, paper-based workflows that often resultin inaccurate records, delayed scheduling, weak data security, and limited communication with parents, increasingthe risk of missed or delayed vaccinations. Despite the proven success of digital immunization systems in otherregions, similar technologies remain underutilized in many local community health centers. This study aims toimprove the effectiveness, accuracy, and efficiency of vaccination record management, scheduling, and vaccineinventory monitoring through the development of a digital health information system known as Vaxi-eTrack. Thestudy employed the Rapid Application Development (RAD) methodology, allowing iterative system design, activeuser involvement, and continuous refinement throughout the development lifecycle. The results revealed SUS scoresranging from 42.5 to 100, indicating varied user experiences but overall positive acceptance. The system achieved astrong overall mean quality score of 4.14 out of 5, with the highest rating in Security, followed by Maintainability,Compatibility, and Scalability, demonstrating strong system performance, reliability, and readiness for broaderdeployment. Overall, Vaxi-eTrack proved to be an effective digital solution for improving immunization tracking,record accuracy, and service delivery in community health settings, and it is recommended that the system beexpanded to other barangays, enhanced with SMS or push notifications, equipped with offline functionality, andcontinuously evaluated to ensure long-term sustainability and improved public health outcomes.